Playing to Pretend or “Pretending” to Play: Play in Children with Autism Spectrum Disorder - Westby, Carol (Seminars in Speech and Language, 2022)
Children diagnosed with autism spectrum disorder (ASD) exhibit early delays and deficits in play. In infancy, they engage in unusual exploratory behaviors with toys. As toddlers, they are slow to develop functional play, and in preschool some children with ASD fail to develop symbolic play despite having the necessary cognitive and language skills. Furthermore, when children with ASD are engaged in play, they demonstrate less playfulness. This article reviews the literature on the characteristics of exploratory, functional, and symbolic/pretend play in children with ASD and possible reasons for their unusual patterns of play development. Increased quantity and quality of play are frequent therapeutic goals for children with ASD. If play interventions are to be successful, it is critical that speech-language pathologists have an adequate assessment of children's play skills. Several frameworks and tools appropriate for assessing play in typical children and children with ASD are described.
Keywords: autism spectrum disorder; theory of mind; functional play; symbolic play; naturalistic developmental behavior intervention